Sacido, Jorge (Ed.). 2012. Modernism, Postmodernism, and the Short Story in English. Amsterdam and New York: Rodopi. Series: Postmodern Studies, 48. 269 pages. ISBN: 9789042035577 - Álvarez Amorós, José Antonio (International Journal of English Studies, 2014)
The debate between Modernism and Postmodernism has been one of the most revisited topics in late twentieth-century and early twenty-first century cultural and critical history ever since Jean-Françoise Lyotard’s Le condition posmoderne (1979) managed to trigger off an enduring interest in the large-scale evolution of Western culture and the nature of knowledge over the past century. (...) doi: http://dx.doi.org/10.6018/ijes/14/1/198071